A New Way of Sensing: Need-Based Activation of Antibiotic Resistance by a Flux-Sensing Mechanism - Georg Fritz (American Society for Microbiology, 2015)
ABSTRACT Sensing of and responding to environmental changes are of vital importance for microbial cells. Consequently, bacteria have evolved a plethora of signaling systems that usually sense biochemical cues either via direct ligand binding, thereby acting as “concentration sensors,” or by responding to downstream effects on bacterial physiology, such as structural damage to the cell. Here, we describe a novel, alternative signaling mechanism that effectively implements a “flux sensor” to regulate antibiotic resistance. It relies on a sensory complex consisting of a histidine kinase and an ABC transporter, in which the transporter fulfills the dual role of both the sensor of the antibiotic and the mediator of resistance against it. Combining systems biological modeling with in vivo experimentation, we show that these systems in fact respond to changes in activity of individual resistance transporters rather than to changes in the antibiotic concentration. Our model shows that the cell thereby adjusts the rate of de novo transporter synthesis to precisely the level needed for protection. Such a flux-sensing mechanism may serve as a cost-efficient produce-to-demand strategy, controlling a widely conserved class of antibiotic resistance systems. IMPORTANCE Bacteria have to be able to accurately perceive their environment to allow adaptation to changing conditions. This is usually accomplished by sensing the concentrations of beneficial or harmful substances or by measuring the effect of the prevailing conditions on the cell. Here we show the existence of a new way of sensing the environment, where the bacteria monitor the activity of an antibiotic resistance transporter. Such a “flux-sensing” mechanism allows the cell to detect its current capacity to deal with the antibiotic challenge and thus precisely respond to the need for more transporters. We propose that this is a cost-efficient way of regulating antibiotic resistance on demand.